Pengaruh Massa Filler-Matriks terhadap Sifat Mekanik dan Daya Serap Air pada Komposit Cangkang Biji Karet - Idhil Ismail, Andi; Rasidah, Rasidah; Haliq, Ridhwan (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2021)
The amount of rubber seed waste in Indonesia is highly yielded as a side product from a large amount of rubber trees plantation. The rubber seed was not processed become the usefull application yet,Â thus it becomes a high volume of waste in each year. An initiative should be done to turn it as a practical material. The rubber seed is potential for natural composite along with the increasing attention toward natural composite application.This work aims to produce natural fibre composite based on rubber seed and characterize it's mechanical properties. In this work, the rubber seed natural composite produced by using the hand lay-up method. Polyester resin YUCALAC BQTN-157 was used as the matrix with the addition of 1% MEKP (Methyl-Ethyl-Ketone- Peroxide) as the catalyst. Mechanical properties of the composite were examined by using a tensile and bending test. Additionally, the water absorption test was performed according to the ASTM D 570. The result showed that the tensile and bending strength decrease with increasing the filler composition, which is added in the composite. The composite, which has the filler composition of 40% was generate the highest tensile strength. In contrast, the lowest tensile strength appeared at the composite with a filler of 60%. The bending strength trend also behaves similarly with the tensile strength as the filler composition increased. Water absorption ability of composites displays the acceptable value as it shows within the range of 2.22-2.96%.